If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -10 = 2x + 18 Reorder the terms: -10 + 3x = 2x + 18 Reorder the terms: -10 + 3x = 18 + 2x Solving -10 + 3x = 18 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -10 + 3x + -2x = 18 + 2x + -2x Combine like terms: 3x + -2x = 1x -10 + 1x = 18 + 2x + -2x Combine like terms: 2x + -2x = 0 -10 + 1x = 18 + 0 -10 + 1x = 18 Add '10' to each side of the equation. -10 + 10 + 1x = 18 + 10 Combine like terms: -10 + 10 = 0 0 + 1x = 18 + 10 1x = 18 + 10 Combine like terms: 18 + 10 = 28 1x = 28 Divide each side by '1'. x = 28 Simplifying x = 28
| -x-24=5+x | | -18d+5d(8+3d)=7(3d-8) | | 5+r=18 | | 16-9(d-5)=-2 | | -148=4(6+7x)-4 | | c+5=41 | | 24=2x+3(2x) | | 5.8=-8+x | | 6(x+4)-5=1 | | 3+5w=9+4w | | -2x+2=-2x+1 | | 7=n/7+9 | | 2n^2-3n+4=0 | | (9x^2)-131x+450=0 | | -3(y-6)=30 | | 2y+x=-9 | | Y+11=-11 | | 5-x-1=x-2 | | Y+11=11 | | 11=3n-10 | | -29x+2=-2x+1 | | -7(b+3)=7 | | (x+18)(x-6)=25 | | 3b-1(6-b)=22 | | x+3x=50000 | | 2r=72 | | 2(x+4)=4+4x | | Z^2-2z-24=0 | | 38(24-3.5x)=16(3x-10)+76.5 | | u^2+u-52=0 | | 3(x+2)=-2(x+4) | | -4(e+6)=-12 |